Pengaruh Etika Pegawai, Pelayanan Publik dan Reformasi Birokrasi terhadap Penerapan Zona Integritas pada Lapas Kelas II A Watampone: The Influence of Employee Ethics, Public Service, and Bureaucratic Reform on the Implementation of Integrity Zones at Class II A Watampone Penitentiary - A Musfirah; Normiyati N; Herniah S; Muhammad Nasir (KAIZEN : Kajian Ekonomi, Manajemen, Akuntansi, dan Kewirausahaan, 2026)
This study examines the effect of Employee Ethics, and Improvement of Public Services on the Implementation of the Integrity Zone. Respondents in this study were Watampone Class II Penitentiary Visitors. The number of visitors who sampled this study was 55 people. The method of determining the sample used in this study is Simple Random Sampling, while the data processing method used by researchers is multiple regression analysis. The results of this study indicate that Employee Ethics and Public Services have a significant effect on the Implementation of the Integrity Zone in Watampone Class II Penitentiary.